1991
DOI: 10.1103/physrevlett.66.1078
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of intrinsic bistability and high-frequency current oscillations in resonant tunneling structures

Abstract: Intrinsic high-frequency oscillations (^2.5 THz) in current and corresponding quantum-well density have been simulated for the first time for a fixed-bias voltage in the negative differential resistance (NDR) region of the current-voltage (I-V) characteristics of a resonant tunneling diode. Scattering and self-consistency are included. Hysteresis and "plateaulike" behavior of the time-averaged I-V curve are simulated in the NDR region. Intrinsic bistability is manifested by the phenomenon of unstable electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
126
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 27 publications
10
126
3
Order By: Relevance
“…A similar I-V curve was obtained by Jensen and Buot. 24) However, while they observed only one plateau region, our results indicate the existence of two plateau regions. In addition, while the oscillation they found does not decay, the oscillation found here does besides the cases in the upper plateau.…”
contrasting
confidence: 67%
See 2 more Smart Citations
“…A similar I-V curve was obtained by Jensen and Buot. 24) However, while they observed only one plateau region, our results indicate the existence of two plateau regions. In addition, while the oscillation they found does not decay, the oscillation found here does besides the cases in the upper plateau.…”
contrasting
confidence: 67%
“…23) Jensen and Buot developed a numerical scheme to treat systems of the same kind and reported that current oscillation and plateau-like behavior arise from intrinsic bistability. 24,25) In the previous studies, dissipative effects of electron transport have been taken into account by using the Boltzmann equation. The quantum version of the Boltzmann equation, however, employs several approximations, and it does not satisfy the fluctuation-dissipation theorem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical work by several other groups predicted the same phenomenon [13][14][15][16] . It has been suggested that the RTD intrinsic current oscillations could circumvent the low-power problem and lead to THz-frequency power in the milli-watt range 12 .…”
Section: Introductionmentioning
confidence: 66%
“…Intrinsic current oscillations in dc-biased RTDs were first observed in numerical calculations by Jensen and Buo 13 , who found that the oscillations were persistent (did not decay over time). Theoretical work by several other groups predicted the same phenomenon [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%